1999
DOI: 10.1136/ip.5.4.264
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting motorcycle helmet use in the population of Greater Athens, Greece

Abstract: Objectives-Helmet use is the best preventive measure available against two wheel motorized vehicle (TWMV) related head injuries. In some countries, however, helmets are used only by a minority of TWMV riders. In collaboration with the Road TraYc Police Department, an inspection survey was undertaken to assess the prevalence and to determine predictors of helmet use. Setting-The Greater Athens area, Greece, during July and August 1998. Methods-A total of 982 TWMVs were stopped, 349 of which had two riders (36%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
61
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 30 publications
18
61
0
3
Order By: Relevance
“…Safety helmet use rates of 16.3% and 13.2% were observed for male and female child pillion riders, respectively. The reported safety helmet use compliance rate [8] for riders is higher than that of the child pillion riders' as in accordance with other studies [9,10,11]. A majority of Malaysian population is aware of the safety helmet law, however the compliance rate is still low among child pillion riders [8].…”
Section: Introductionsupporting
confidence: 73%
“…Safety helmet use rates of 16.3% and 13.2% were observed for male and female child pillion riders, respectively. The reported safety helmet use compliance rate [8] for riders is higher than that of the child pillion riders' as in accordance with other studies [9,10,11]. A majority of Malaysian population is aware of the safety helmet law, however the compliance rate is still low among child pillion riders [8].…”
Section: Introductionsupporting
confidence: 73%
“…In common with the majority of studies, we identified an excess risk of accident involvement among novice PTW riders (Chang and Yeh 2006;Evans 2004;Harrison and Christie 2005;Lardelli-Claret et al 2005;Lin et al 2003;Mullin et al 2000;Reeder et al 1995;Rutter and Quine 1996;Ryan et al 1998;Skalkidou et al 1999;Yannis et al 2005). This may be due to a combination of young people's inexperience and risk-taking (Chesham et al 1993;Ryan et al 1998) as well as risk exposure (Harrison and Christie 2005;Yannis et al 2005).…”
Section: Discussionmentioning
confidence: 81%
“…Weather conditions, type of road, circulation area and time of the day are some of the variables identifi ed as factors associated with helmet use. 5 Likewise, some individual-related variables have been defi ned as markers of differences among people sharing the same background and environment such as education level, gender and age. 1 Other individual-related variables infl uencing helmet use are closely related to the road user profi le including having or not having a driver's license, type of motorcycle, among others.…”
Section: Introductionmentioning
confidence: 99%